Peningkatan Kesadaran Orang Tua dalam Pencegahan Anak Putus Sekolah Melalui Sosialisasi dan Pendampingan Edukatif di Desa Kemiri - Ahmat Aftoni; Desi Duwi; Bella Intan; Vito Aprilian; Winda Ayu Oktaviana; Bekham Sholeh; Ida Fitriawati; Asmuni Asmuni; Rohim Rohim (Civiliza Publishing, 2025)
The problem of school dropouts remains a significant issue in educational development in rural areas. The contributing factors include family economic limitations, low parental awareness of the importance of education, and a social environment that inadequately supports children's learning continuity. A study conducted in Sodong and Kantong Hamlets, Kemiri Village, Panti District revealed a school dropout risk rate of 45% before intervention. This community service program aims to reduce the risk of school dropouts through strengthening the role of families and enhancing student learning motivation. The implementation methods include field observation, program planning, socialization with parents through community groups, student mentoring through an educational roleplay approach, as well as monitoring and evaluation. The program was implemented collaboratively, involving students, village officials, school staff, and local community members. Evaluation results demonstrated significant improvements: learning motivation levels and commitment to continuing school increased from 45% to 80%, accompanied by increased parental understanding of the importance of education, positive behavioral changes in students, enhanced learning motivation, improved discipline, and increased self-confidence. The community empowerment approach combined with interactive communication proved effective in strengthening collective awareness regarding the importance of education. This initiative is expected to serve as a sustainable community service model that can be replicated in other rural areas.